Pengembangan Buku Panduan Pembelajaran Metode Proyek Untuk Guru TK - Widayanti, Melia Dwi; Abidin, Muhammad Zainal (THUFULA, 2020)
DEVELOPING PROJECT METHOD LEARNING GUIDEBOOK FOR AL-HIKMAH’S KINDERGARTEN TEACHER. Every teacher needs to develop their proffesionality. Preschool teacher should know how to implement suitable method for their student. In this study, we develop a project method learning guidebook for preschool teacher to help them implement project method in class. It contains of information about project method and some example of project method activities. This is Research and Development that used ADDIE model. ADDIE model consists of Analyze, Design, Development, Implementation, and Evaluation. Content expert, media expert was involved in this study to give their opinion and assesing the guidebook. Data analys is technique that used in this research are quantitative and qualitative. The result shows that project method learning guidebook get “Very Good” category by media expert and content expert. From that finding, it can conclude that project method learning guidebook can be used for preschool teacher to implement project method in their class.